2004
DOI: 10.1126/science.1098876
|View full text |Cite
|
Sign up to set email alerts
|

Intercontinental Spread of Pyrimethamine-Resistant Malaria

Abstract: Here we present molecular evidence demonstrating that malaria parasites bearing high-level pyrimethamine resistance originally arrived in Africa from southeast Asia. The resistance alleles carried by these migrants are now spreading across Africa at an alarming rate, signaling the end of affordable malaria treatment and presenting sub-Saharan Africa with a public health crisis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
396
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 466 publications
(425 citation statements)
references
References 10 publications
25
396
2
2
Order By: Relevance
“…There is evidence of recent selective sweeps across specific regions of the genome, presumably as a consequence of recent drug pressure (Wootton et al, 2002;Nair et al, 2003;Roper, 2003;Roper, 2004). Older selective sweeps as a consequence of natural selection may have occurred across the genome, but identification of these regions might require a genome-wide haplotype map and analysis of linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence of recent selective sweeps across specific regions of the genome, presumably as a consequence of recent drug pressure (Wootton et al, 2002;Nair et al, 2003;Roper, 2003;Roper, 2004). Older selective sweeps as a consequence of natural selection may have occurred across the genome, but identification of these regions might require a genome-wide haplotype map and analysis of linkage disequilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…Regions of the genome that have undergone recent selective sweeps include regions of chromosome 7 surrounding the pfcrt locus (Wootton et al, 2002) and regions of chromosome 4 surrounding the dhfr (Nair et al, 2003;Roper et al, 2003) and dhps (Roper et al, 2004) loci. These selective sweeps are recent in the evolutionary history of P. falciparum, presumably because they are a consequence of recently applied drug pressure.…”
Section: Introductionmentioning
confidence: 99%
“…They detected several selective sweeps associated with CQ resistance, including the previously described region on chromosome 7 containing pfcrt, as well as loci on chromosomes 5 (harboring the multidrug resistance gene homolog pfmdr1) and 11. Focusing on pyrimethamine resistant clones, they were able to detect two candidate selective sweeps on chromosomes 13 and 14, which were of particular interest because they demonstrated a stronger signal than the previously identified sweep at the dhfr locus on chromosome 4 [9,13,14].…”
Section: Genomic Studies Using Polymorphisms To Identify Resistance Locimentioning
confidence: 95%
“…Roper et al [9] analyzed microsatellites surrounding alleles of the dihydrofolate reductase (dhfr) gene that confer resistance to pyrimethamine. They concluded that the most resistant form of dhfr commonly found in Africa, characterized by three point mutations, was associated with a set of related haplotypes that originated in Southeast Asia (Figure 1).…”
Section: Genomic Studies Using Polymorphisms To Identify Resistance Locimentioning
confidence: 99%
“…[50][51][52][53][54][55] In the past, drug-use patterns in Africa readily fostered partly resistant parasites, but highgrade resistance originated from Asia. 56,57 Drug-use patterns in Africa have changed substantially in the past decade and much investment has been made to improve availability of drugs and provision of chemoprevention for vulnerable groups. De-novo emergence of resistance is most likely to occur in areas of low transmission, low immunity, and high parasite load in infected individuals, where a high proportion of infected people have symptoms and seek treatment.…”
Section: Parasite Resistancementioning
confidence: 99%